Determining Helicopter Blade Length Per Airworthiness Strength Requirement - Sariman, Nur Ika Farhana (Universiti Sains Malaysia, 2017)
This paper demonstrates a methodology to determine the length of a metal helicopter rotor blade operating at 500 RPM so that it fulfills the airworthiness strength requirement. To achieve this, stress analyses were performed on different blade length using SOLIDWORKS 2016 x64 Edition. The NACA 8-H-12 airfoil sections with a 5.25 inches uniform chord length was chosen; suitable as rotor-blade sections for helicopters and other rotary-wing aircraft due to previous investigation. The capability of the structure to withstand maximum operating load were observed and checked. Focusing only for rigidly mounted (clamped root joint) helicopter rotor blade analysis. Result obtained from the analysis showed that 2 m (78 in) length of rotor blade is acceptable length and fulfills the airworthiness strength requirement.